“I am one dedicated person working for freedom”: Septima P. Clark’s Contributions to Social Justice Adult Education at Highlander Folk School - Lisa M. Baumgartner (Adult Education Research Conference, 2006)
This paper unearths Septima P. Clark’s contributions to adult education efforts at Highlander Folk School. Autobiographical texts and archival holdings were analyzed through a critical, feminist lens to determine her contributions. In addition, the adult education strategies she utilized in her work were examined using a Freireian framework.
Keywords: Septima P. Clark; social justice; Highlander Folk School